Interaction between piperazine and chlorpromazine - Sturman, Gillian (1974)
The interaction between piperazine and chlorpromazine has been studied in rats and mice. Piperazine administered a few hours previously potentiated the action of chlorpromazine on the central nervous system. No such interaction was found between piperazine and prochlorperazine.